ISLAMIC MANUSCRIPT CULTURE AND TRANSREGIONAL MUSLIM INTELLECTUAL NETWORKS IN MINDANAO AND SOUTHEAST ASIA - Willem van der Molen; Irina R. Katkova; Edwin Wieringa (Tunas Harapan Ummat Foundation, 2026)
This article addresses a significant gap in the historiography of Islam in Mindanao, southern Philippines, by examining the intellectual and religious networks that shaped Muslim scholarly traditions in the region during the nineteenth century. Although Islamic institutions and practices had long been established in Mindanao, the extent of their intellectual connections with broader Muslim scholarly circles has remained insufficiently explored. The present study focuses on a recently identified corpus of Islamic manuscripts discovered in the Mindanao region by scholars such as Annabel Teh Gallop, Oman Fathurahman, and Kawashima Midori. These manuscripts once belonged to a prominent Maranao scholar, Shaykh Aleem Ulomuddin Said, and constitute an important body of primary sources for understanding the intellectual history of Islam in the region. The collection comprises texts written in Malay, Arabic, and Maranao and encompasses a wide range of Islamic disciplines, including Qurʾānic studies, ḥadīth, tafsīr, Sufism (taṣawwuf), ritual prayer, amulets (ajimat), theology and creed (ʿaqīdah), as well as Arabic morphology. Employing a qualitative research design combined with philological analysis of the manuscript materials, this study investigates the intellectual content and transmission patterns reflected in these texts. The findings demonstrate that the manuscripts reveal extensive scholarly linkages between Muslim communities in Mindanao and other centres of Islamic learning within the Malay world, particularly Aceh, Banten, Cirebon, and Minangkabau. Furthermore, the materials indicate connections with the wider Islamic intellectual sphere in the Middle East, including Mecca, Medina, and Yemen, mediated in part through the transregional Sufi network of the Shaṭṭārīyah order. These connections contributed to the circulation of religious knowledge and played a crucial role in shaping Islamic intellectual traditions in Mindanao well into the nineteenth century.